Collaborations between Translational Science Programs and Academic Health Sciences Libraries - Holmes, Kristi; Deaver, Jill; Surkis, Alisa; Whipple, Elizabeth C; von Isenburg, Megan; Burks, Sandra; Glenn, Emily; Ragon, Bart (University of Virginia, 2025)
Collaborations between translational science programs and academic health sciences libraries enhance research impact by improving efficiency, leveraging diverse professional expertise, and expanding opportunities for collaboration. Utilizing a team science approach, this study integrates findings from literature reviews, practical experiences of health sciences librarians, and collaborative writing. Analysis of case studies from institutions with successful partnerships highlights the roles of libraries in supporting translational science programs. Data mapping to the Clinical and Translational Science Award Program’s functional areas reveals opportunities for effective collaboration. Results demonstrate improved research workflows, increased interactions between researchers and libraries, and accelerated translation of discoveries into clinical settings. These partnerships illustrate best practices for other institutions aiming to support translational science, driving innovation and amplifying contributions from both libraries and translational science programs.
This work was supported, in part, through the following National Institutes of Health NCATS and National Institute of General Medical Sciences grants: UL1TR003015, UM1TR004926, UM1TR004402, UL1TR001445, UL1TR002319, UM1TR004771, UL1TR001857, U54GM115458, U54GM115428, UL1TR002553, UL1TR001872, U54GM115677, UL1TR00200, UL1TR002389, UL1TR002384, UM1TR005121.
Original submission date: 2025-04-07T14:57:07Z
Keywords: Translational Science